The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/brainsci11060707
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Transcranial Direct Current Stimulation in Enhancing Surgical Skill Acquisition: A Preliminary Meta-Analysis of Randomized Controlled Trials

Abstract: The application of transcranial direct current stimulation (tDCS) to targeted cortices has been found to improve in skill acquisition; however, these beneficial effects remained unclear in fine and complicated skill. The aim of the current meta-analysis was to investigate the association between tDCS application and the efficacy of surgical performance during surgical skill training. We included randomized controlled trials (RCTs) investigating the efficacy of tDCS in enhancing surgical skill acquisition. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Indeed, they have demonstrated their efficacy on improving the inhibitor control when targeting PFC, both in healthy and SUD subjects [70][71][72]. It could also be explained by the neural noise hypothesis, according to which tDCS may improve cognitive performance not only through cortical activity modulation but also via modification of the synaptic activity of neurotransmitters in general (such as dopamine, glutamate or serotonin) by activation of various cortices in addition to the targeted ones [73].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they have demonstrated their efficacy on improving the inhibitor control when targeting PFC, both in healthy and SUD subjects [70][71][72]. It could also be explained by the neural noise hypothesis, according to which tDCS may improve cognitive performance not only through cortical activity modulation but also via modification of the synaptic activity of neurotransmitters in general (such as dopamine, glutamate or serotonin) by activation of various cortices in addition to the targeted ones [73].…”
Section: Discussionmentioning
confidence: 99%
“…The nomenclature and classification of treatment arms were named according to our previous seven NMAs of NIBS in different diseases. 6,[25][26][27][28][29][30] The nomenclature of brain mapping was based on 10-20 EEG mapping (i.e. F3 for left DLPFC, Fp1 for left vmPFC, and F4 for right DLPFC).…”
Section: Data Extractionmentioning
confidence: 99%
“…Here, neuroplasticity is the ability of the central nervous system to respond to intrinsic or extrinsic stimuli by reorganizing its structure, function, and connections. Recently, Hung et al [11] Brain Sci. 2021, 11, 1078 2 of 6 presented the first preliminary meta-analysis of randomized control trials that showed that tDCS was associated with significantly better improvement in surgical performance than the sham control.…”
mentioning
confidence: 99%
“…2021, 11, 1078 2 of 6 presented the first preliminary meta-analysis of randomized control trials that showed that tDCS was associated with significantly better improvement in surgical performance than the sham control. Hung et al [11] found that tDCS over the bilateral prefrontal cortex (PFC) and the primary motor cortex (M1) were both associated with significantly better improvements in surgical performance. Since complex motor tasks [12] involve motor control and attention-related brain areas, it is expected that both the PFC and M1 stimulation may facilitate task performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation